Modelling of the welded seam parameters at electron-beam welding. Issue 2 (November 2018) - Seregin, Yu N; Murygin, A V; Tynchenko, V S; Milov, A V
Abstract: The article presents the results of technological parameters mathematical modeling when heating a titanium alloy by energy sources equivalent to an electron beam in electron-beam welding. Analysis and evaluation of simulation results was carried out using the criterion of optimality proposed by the authors. As a tool for calculations, the authors used a functional based on mathematical models of metal heating by a complex heat source consisting of mobile instantaneous point and linear energy sources. The results of calculations for a 0.12 cm thick plate are given in the paper. They were compared with the data obtained from prototypes from the VT-14 material using the design welding regimes carried out in the laboratory on an A306.13 electron beam unit.